Víxlmengun á tannsmíðaverkstæðum - Árdís Olga Sigurðardóttir; Ellen Flosadóttir; W. Peter Holbrook (Tannlæknafélag Íslands, 2014)
Efst á síðunni er hægt að nálgast greinina í heild sinni með því að smella á hlekkinn Infection risk from pumice used in the dental laboratory has attracted attention but no information on this issue has been available in Iceland. The aim of this study was to evaluate the use of dental pumice for the risk of cross contamination between patients, dental technicians and other dental health professionals. The study aimed to answer the following research questions: What is the disinfection policy of dental laboratories in order to reduce the risk of cross-contamination and how important is disinfecting pumice to reduce contamination of dental materials with which dental technicians work. Methods: The study was quantitative using relevant statistics. A questionnaire was sent out via email to all existing members of the Icelandic Dental Technicians’ Association. Samples of pumice were collected from seven dental laboratories and also from the clinic of the Faculty of Odontology of the University of Iceland. 8 Results: Results showed that dental laboratories were not properly disinfected in order to be sure of reducing the risk of cross-contamination. The survey questionnaire showed that about 90% of dental technician work places used the same pumice for repairs and new prostheses. Furthermore 50% of technicians simply added pumice when needed. Results from pumice samples showed far fewer environmental bacteria and other microorganisms from the dental technician equipment in the clinic of Faculty of Odontology of the University, where pumice was changed regularly, usually every day. The survey showed that 45% of dental technicians did not know if the prosthesis they were working with had been disinfected after leaving the dental clinic. Conclusion: It is important to use an antiseptic agent for pumice and also to disinfect the prostheses, impressions and other similar material before they are sent to the dental technician and also before the dental technician delivers the prosthesis to the dental clinic.